Ringo Saves the Day! - Clements, Andrew; 1949-; Beier, Ellen (New York, 2001)
A young woman and her husband are glad that they gave a stray kitten a home when it saves their lives by alerting them to a gas leak.
Keywords: Cats; Anecdotes; Cats; Pets